Eksplorasi Etnomatematika pada Tradisi Bandongan dan Sorogan di Pondok Pesantren: Kajian Konsep Barisan dan Pola Bilangan - Najwa Layali Tama; Faiz Fauziyah; Rismatus Sholikhah; Sofi al -hakim; Muhammad Hasan Asnawi (PT Cendekia Education Center, 2026)
This study aims to explore the mathematical concepts embedded in the Bandongan and Sorogan traditions of Islamic boarding schools (pondok pesantren), particularly the concepts of number sequences and patterns, as well as to examine their potential as a contextual and meaningful source of mathematics learning for santri (students of Islamic boarding schools) and students in general. The research employed a descriptive qualitative approach with an ethnographic design, in which the researcher was directly involved in observing the Bandongan and Sorogan activities carried out within the pesantren environment. Data were collected through participatory observation, semi-structured interviews with kiai (Islamic scholars/leaders), ustadz (teachers), and santri, as well as documentation of learning activities. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing, referring to the Miles and Huberman model. The results show that the Bandongan tradition contains the concept of number patterns in the sequential order of delivering kitab (religious text) material, which is arranged in a tiered manner, while the Sorogan tradition reflects the concept of sequences in the santri turn-taking system, which follows a particular order based on the level of material mastery. These findings contribute an alternative source of local culture-based mathematics learning that can enrich the teaching of sequence and number pattern concepts in schools, while also reinforcing the understanding that religious practices and pesantren traditions are closely connected to formal mathematical concepts.